Effects of Mg17Al12 second phase particles on twinning-induced recrystallization behavior in Mg‒Al‒Zn alloys during gradient hot rolling. Issue 9 (September 2019) - Jin, Zhong-Zheng; Cheng, Xiu-Ming; Zha, Min; Rong, Jian; Zhang, Hang; Wang, Jin-Guo; Wang, Cheng; Li, Zhi-Gang; Wang, Hui-Yuan
Abstract: This study aims to investigate the promotion effect of twinning-induced nucleation vs the inhibition effect of Mg17 Al12 particles pinning for recrystallization, achieved through gradient rolling for Mg‒3Al‒1Zn (AZ31) and Mg‒9Al‒1Zn (AZ91) alloys as well as pure Mg. Through gradient rolling, a transition zone from the initial to deformed microstructure undergoing varying thickness reductions was obtained in the same sample, where the evolution of deformation twins and second phase can be examined precisely and continuously. During hot deformation, dynamic recrystallized (DRXed) grains tended to originate from {10 1 ¯ 1}-{10 1 ¯ 2} double twins, whose nucleation was significantly restricted by increasing Al content and hence recrystallization can be rarely triggered in AZ91 alloy. Concurrently, the size and volume fraction of Mg17 Al12 particles changed via dissolution and re-precipitation, leading to finer average size and higher volume fraction, which produced stronger pinning effect and hindered dynamic recrystallization significantly. The current study provides insights into the mechanisms responsible for dynamic recrystallization behavior during hot rolling in Mg‒Al‒Zn alloys.